Effect of hydraulic retention time on organic removal and biofilm development in gravity-driven membrane filtration for rainwater treatment - Soon, Genevieve Qian Yi (2018)
Water scarcity is a pressing issue that a large part of the world faces. Rainwater harvesting has been used for decades as a source of water, particularly in areas with few water catchments, or lack advanced technologies to treat water. However, even for non-potable use, it needs to be treated as it contains bacteriological contaminants. There is huge potential for gravity-driven membrane (GDM) filtration to be used for rainwater treatment as it has low operating costs, does not require a centralized water system and frequent chemical cleanings. This is due to its unique characteristic of a biofouling layer formed on the membrane surface. The objective of this study was to examine the effect of hydraulic retention time and short-term backwashing on membrane performance and permeate quality of submerged GDM filtration systems for rainwater treatment. Results showed that hydraulic retention time and backwashing period did not have a significant impact on membrane performance. Furthermore, for all the backwash periods, the recovery in permeate flux was temporary and returned to the original flux within a day, and was lower than the flux of the membrane without backwashing. This implies that the biofilm/cake layer has a significant role in flux stabilization and the removal of this layer through backwashing will decrease the permeate quality and membrane performance.